Design of the End-effector of Waste Lithium-ion Battery Handling Robots - Zhang Hongsheng; Deng Ze (Jixie chuandong)
In order to solve the problem of waste lithium-ion battery recycling, a robot end-effector is designed to carry the battery weight and adapt to different sizes in the process of sorting. In this study, each mechanism of the end-effector is introduced. The kinematic model of the six-bar mechanism is established by further checking the toe-bar six-bar mechanism. The rod length and position parameters of six-bar mechanism are optimized by genetic algorithm-BFGS （GA-BFGS） quasi-Newton method and particle swarm optimization-BFGS (PSO-BFGS) quasi-Newton method, and the dynamics model of the six-bar mechanism is established. The driving force required by no load and the radial force in the handling process under the limit condition are calculated and simulated. This study provides a new idea of the six-bar drive mechanism, and provides reference for the research and development of the waste lithium-ion battery sorting equipment.